Integrated Photodetectors Based on Group IV and Colloidal Semiconductors: Current State of Affairs - Principia Dardano; Maria Antonietta Ferrara (Micromachines, 2020)
With the aim to take advantage from the existing technologies in microelectronics, photodetectors should be realized with materials compatible with them ensuring, at the same time, good performance. Although great efforts are made to search for new materials that can enhance performance, photodetector (PD) based on them results often expensive and difficult to integrate with standard technologies for microelectronics. For this reason, the group IV semiconductors, which are currently the main materials for electronic and optoelectronic devices fabrication, are here reviewed for their applications in light sensing. Moreover, as new materials compatible with existing manufacturing technologies, PD based on colloidal semiconductor are revised. This work is particularly focused on developments in this area over the past 5–10 years, thus drawing a line for future research.